Carbon nanotube scaffolds with controlled porosity as electromagnetic absorbing materials in the gigahertz range. Issue 20 (6th May 2016) - González, M.; Crespo, M.; Baselga, J.; Pozuelo, J.
Abstract : The porous structure of CNT nanocomposites allows modulation of the electromagnetic shielding. Abstract : Control of the microscopic structure of CNT nanocomposites allows modulation of the electromagnetic shielding in the gigahertz range. The porosity of CNT scaffolds has been controlled by two freezing protocols and a subsequent lyophilization step: fast freezing in liquid nitrogen and slow freezing at −20 °C. Mercury porosimetry shows that slowly frozen specimens present a more open pore size (100–150 μm) with a narrow distribution whereas specimens frozen rapidly show a smaller pore size and a heterogeneous distribution. 3D-scaffolds containing 3, 4, 6 and 7% CNT were infiltrated with epoxy and specimens with 2, 5 and 8 mm thicknesses were characterized in the GHz range. Samples with the highest pore size and porosity presented the lowest reflected power (about 30%) and the highest absorbed power (about 70%), which allows considering them as electromagnetic radiation absorbing materials.